Tinjauan Hukum Terhadap Kepemilikan Saham Dalam Perseroan Terbatas Sebagai Harta Waris - Andyna Susiawati Achmad; Astrid Athina Indradewi (Fakultas Hukum, Universitas Warmadewa, 2025)
Inheritance of shares in a Limited Liability Company is a form of legal transfer of rights that occurs automatically upon the death of the testator, as regulated in the Civil Code (KUHPer) and specifically in Law Number 40 of 2007 concerning Limited Liability Companies (UUPT). However, in practice, the inheritance of shares does not always run smoothly because it can cause problems, especially if there are objections from other shareholders who refer to the provisions in the Company's Articles of Association. This objection is often based on concerns that it will disrupt the stability and direction of the company's leadership. Therefore, it is important to examine in depth how the mechanism of inheritance of shares can still guarantee the rights of heirs without neglecting the continuity and business interests of the Limited Liability Company itself. This study uses a normative legal research method with a statutory and conceptual approach, and aims to collect and analyze relevant secondary data. The results of the study indicate that the inheritance of shares in a Limited Liability Company must be placed within a legal framework that not only respects the civil rights of heirs, but also takes into account the collective interests of shareholders and the sustainability of the company's operations as a whole. Thus, it is necessary to harmonize positive legal provisions and internal company practices to create justice and legal certainty for all interested parties.